Applied Cryptography and Network Security 4th International Conference, ACNS 2006, Singapore, June 6-9, 2006, Proceedings - Zhou, Jianying; Yung, Moti; Bao, Feng (Security and Cryptology, 2006)
The 4th International Conference on Applied Cryptography and Network Security(ACNS 2006)washeldin Singapore,during June6-9,2006.ACNS 2006 brought together individuals from academia and industry involved in multiple research disciplines of cryptography and security to foster exchange of ideas. This volume (LNCS 3989) contains papers presented in the academic track. ACNS was set a high standard when it was initiated in 2003. There has been a steady improvement in the quality of its program in the past 4 years: ACNS 2003 (Kunming, China), ACNS 2004 (Yellow Mountain, China), ACNS 2005 (New York, USA), ACNS 2006 (Singapore). The average acc- tance rate is kept at around 16%. We wish to receive the continued support from the community of cryptographyand security worldwide to further improve its quality and make ACNS one of the leading conferences. The Program Committee of ACNS 2006 received a total of 218 submissions fromallovertheworld,ofwhich33wereselectedforpresentationattheacademic track. In addition to this track, the conference also hosted an industrial track of presentations that were carefully selected as well. All submissions were reviewed by experts in the relevant areas. We are indebted to our Program Committee members and the external reviewers for the great job they have performed. The proceedings contain revised versions of the accepted papers. However, revisions were not checked and the authors bear full responsibility for the content of their papers.